2002
DOI: 10.1164/rccm.2112043
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life and Mortality in Male Patients with Chronic Obstructive Pulmonary Disease

Abstract: To assess whether generic and specific health-related quality of life (HRQL) are independently associated with total and specific mortality in patients with chronic obstructive pulmonary disease (COPD), we followed until 1999 a cohort of 321 male patients with COPD, recruited in 1993-1994 at outpatient respiratory clinics. Baseline characteristics recorded under stable clinical conditions included forced spirometry, arterial blood gas tensions, dyspnea scales, 11 comorbid conditions, St. George's Respiratory Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
216
4
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(240 citation statements)
references
References 24 publications
10
216
4
10
Order By: Relevance
“…5,8,11,24 The relatively low mortality rate is likely due to the fact that patients were recruited from outpatient clinics, not from hospitals settings 25 where mortality rates can be up to 49% at 2 years. 26 FEV 1% had the strongest association with mortality in our study, a relationship that has been observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,11,24 The relatively low mortality rate is likely due to the fact that patients were recruited from outpatient clinics, not from hospitals settings 25 where mortality rates can be up to 49% at 2 years. 26 FEV 1% had the strongest association with mortality in our study, a relationship that has been observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to improve the use of these predictive models, they need to include variables that are easily gathered in busy clinical practices. Although health-related quality of life (HRQoL) has been shown to be an independent predictor of mortality in patients with COPD, 11 not all HRQoL measurement instruments appear to behave in the same way. 12 Few studies have compared St. George's Respiratory Questionnaire (SGRQ) and the Chronic Respiratory Questionnaire (CRQ) for assessing prognosis in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…COPD is highly prevalent [2], responsible for 2.7 million deaths globally in 2000 [3], and associated with increased morbidity and mortality as well as a reduced quality of life [4,5]. The 1997…”
Section: Introductionmentioning
confidence: 99%
“…The activity component is the strongest predictor of death among the four scores of the SGRQ: Symptom, Activity, Impact, and Total score (ref. 24 ). It is difficult to select the most accurate activity scoring system as they are not widely used in COPD.…”
Section: Components Of Copd Prognostic Scorementioning
confidence: 99%